Potensi madu dan propolis lebah Tetragonula laeviceps dalam menghambat pertumbuhan in vitro bakteri Staphylococcus aureus dan Escherichia coli - Putra, Fernando; Ramona, Yan; Wijaya, I Made Saka (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANA, 2022)
Honey, which is good for human health due to its high nutrition content, is a product of bees that belongs to Tetragonula laeviceps . Besides honey, these bees also produce several derivative products, such as propolis , often used as a health supplement. Honey and propolis have been widely reported to have antimicrobial activity. Therefore, the main aim of this study was to investigate their effectiveness in inhibiting Staphylococcus aureus and Escherichia coli in various in vitro tests (including determination of MIC and LC 50 values). This study used a complete randomized design with five levels of concentrations (15%, 20%, 30%, 40%, and 50% v/v) to determine these two bee’s products ini inhibiting the in vitro growth of S. aureus and E. coli . Ethanol (95% ethanol) used as the solvent in this five replicated experiment, served as nil control. Inhibition zone and MIC values ??were determined by applying the diffusion well method. In contrast, a pour plate method on a nutrient agar medium was applied in the determination of LC 50 values of the honey and propolis . The results of the preliminary study showed that honey of 100% concentration inhibited the growth of S. aureus and E. coli with inhibition zones of 12.50±1.09 mm and 6.60±0.60mm, respectively. Similar results were also shown by propolis with inhibition diameters of 15.50±1.08mm and 8.10±1.00mm on respective lawns of S. aureus and E. coli. Both honey and propolis appeared to have MIC value of 15% (v/v), while their LC 50 values ??on S. aureus were 35.15% (v/v) and 18.25% (v/v), respectively, and on E. coli were 35.89% (v/v) and 28.2% (v/v), respectively. Propolis has a stronger inhibitory effect against S. aureus and E. coli when compared to honey.